1965
DOI: 10.1128/am.13.2.227-231.1965
|View full text |Cite|
|
Sign up to set email alerts
|

Role of Leuconostoc mesenteroides in Leavening the Batter of Idli, a Fermented Food of India

Abstract: The fermentation of the batter of idli, a fermented food of India, was studied. The microorganisms responsible for the characteristic changes in the batter were isolated and identified. Although there is a sequential change in the bacterial flora, the predominant microorganism responsible for souring, as well as for gas production, was found to be Leuconostoc mesenteroides . In the later stages of fermentation, growth of Streptococcus faecalis and, still later, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 1 publication
0
17
0
Order By: Relevance
“…Even though the fermentation temperature varied between 25 and 37 °C, the same observation has been recorded in several studies (Rajalakshmi and Vanaja, 1967;Soni and Sandhu, 1989;Soni and Sandhu, 1990;Ghosh and Chattopadhyay, 2012;Thakkar et al, 2015). The increasing acidity in idli batter mainly depends on Streptococcus faecalis as it produces lactic acid and reduces the pH, increases CO2 concentration in the batter, which leavens batter property (Mukherjee et al, 1965). With the growth of LAB, the pH of batter decreases (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the fermentation temperature varied between 25 and 37 °C, the same observation has been recorded in several studies (Rajalakshmi and Vanaja, 1967;Soni and Sandhu, 1989;Soni and Sandhu, 1990;Ghosh and Chattopadhyay, 2012;Thakkar et al, 2015). The increasing acidity in idli batter mainly depends on Streptococcus faecalis as it produces lactic acid and reduces the pH, increases CO2 concentration in the batter, which leavens batter property (Mukherjee et al, 1965). With the growth of LAB, the pH of batter decreases (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have shown that Idli batter has LAB with probiotic potential. Those strains are Lactobacillus collinoides (Patel et al, 2012), Lueconostoc mesenteroides, Streptococcus faecalis, Pediococcus cerevisiae (Mukherjee et al, 1965), Lactobacillus delbrueckii (Soni et al, 1986) and Lactococcus lactis, Lactobacillus plantarum (Iyer et al, 2011). The antibiotic sensitivity of probiotic microorganisms is an important characteristicin determining their suitability for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…The fermentation period must allow a definite leavening (two-to threefold increase in volume) of the batter and development of a pleasant acid fl avor. The fermented batter is poured into small cups (8 to 10 cm in diameter) and steamed in a covered pan to yield a soft, spongy product (39). The open texture is attributed to the protein (globulin) and polysaccharide (arabinogalactan) in black gram (71).…”
Section: Idlimentioning
confidence: 99%
“…L. mesenteroides is the most commonly encountered bacterium, followed by Lb. fermentum, Enterococcus faecalis, and Pediococcus dextrinicus (39). During fermentation, along with L. mesenteroides, yeasts such as S. cerevisiae, Debaryomyces hansenii, Pichia anomala, and Trichosporon pullulans are predominant, and Trichosporon cutaneum develops subsequently.…”
Section: Idlimentioning
confidence: 99%
“…The fermentation of idli demonstrates a leavening action caused by the activity of the heterofermentative lactic acid bacterium, Leu. mesenteroides (Mukherjee et al, 1965). Soni and Sandhu (1989) enumerated lactic acid bacteria in the fermented batter and found them ranging from 10 6 -10 9 /g that included Leuconostoc mesenteroides, Enterococcus faecalis, Lactobacillus fermentum and Pediococcus cerevisiae essential for leavening of batter and acid production in idli.…”
Section: Introdcutionmentioning
confidence: 99%